THE SYNDROME OF CONSTANT HUNGER - Rajs, Monika; Przebieradło, Patrycja; Rędzianiak, Patrycja; Żak, Sandra; Ruzik, Alicja; Gaj-Hunter, Antonina; Kowalska, Monika; Żurek, Katarzyna; Stolarska, Kaja; Terpiłowska, Sandra (International Journal of Innovative Technologies in Social Science, 2026)
Prader–Willi syndrome (PWS) is a rare genetic disorder resulting from abnormalities in gene expression. The inability to experience satiety constitutes the major challenge faced by individuals affected by this condition. This lifelong disturbance manifests through numerous complications, including morbid obesity, hypogonadism, infertility, diabetes mellitus, hypercholesterolemia, arterial hypertension, cardiovascular diseases, obstructive sleep apnoea, degenerative joint disease, immobility and even social stigmatization due to excessive body weight.The disease and its secondary complications significantly impair the quality of life and contribute to a reduced life expectancy. Although Prader–Willi syndrome is an uncommon clinical entity, the severity and complexity of its manifestations require continuous and coordinated efforts from physicians and healthcare professionals.